2020
DOI: 10.1002/ajhb.23505
|View full text |Cite
|
Sign up to set email alerts
|

Digit ratio (2D:4D) is not related to cardiovascular diseases or their risk factors in menopausal women

Abstract: Objectives Digit ratio (2D:4D) is widely used as a biomarker of prenatal hormonal environment linked to the growing number of adult health and disease‐related characteristics. It has been suggested that 2D:4D is a good predictor of cardiovascular diseases (CVD) risk among men, but results in women are still inconclusive. Here we test the relationship between 2D:4D and the incidence of cardiovascular diseases (CVD), and their risk factors in Polish, rural women. Methods The participants were 410 women age 50 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…This suggestion is evidenced in previous studies where an increased 2D : 4D ratio was associated with a reduced risk of metabolic syndrome and/or its complications [20,21]. However, other studies found higher 2D : 4D in patients with metabolic syndrome and/or its severity, while some found no significant relationships [10][11][12][13][14][15][16][17][18][19]. The incidence and the early onset of cardiometabolic diseases have also been found to be relatively higher in males than in premenopausal females.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…This suggestion is evidenced in previous studies where an increased 2D : 4D ratio was associated with a reduced risk of metabolic syndrome and/or its complications [20,21]. However, other studies found higher 2D : 4D in patients with metabolic syndrome and/or its severity, while some found no significant relationships [10][11][12][13][14][15][16][17][18][19]. The incidence and the early onset of cardiometabolic diseases have also been found to be relatively higher in males than in premenopausal females.…”
Section: Discussionmentioning
confidence: 87%
“…Despite the inconclusive nature of previous studies, some authors sought to determine the association between the 2D : 4D ratio and risk factors for cardiometabolic diseases such as fasting plasma lipid parameters and anthropometric variables. While some authors have reported a positive relationship between the 2D : 4D ratio and the risk of cardiometabolic diseases, others found the reverse or no significant relationship [10][11][12][13][14][15][16][17][18][19][20][21]. However, a previous study found a significant positive correlation between triglycerides and the 2D : 4D ratio of both hands [22].…”
Section: Introductionmentioning
confidence: 99%
“…This may no longer seem incongruous to the modern audience as there is now ample evidence accumulating that demonstrates the association of noninvasive phenotypes with disease risk. For instance, the relatively innocuous measures, like the 2D/4D finger length ratio is highly informative in predicting many diverse outcomes, such as risk for cardiovascular diseases, Attention deficit hyperactivity disorder ADHD, and behavioral traits, and so on (Manning et al, 1998 ; Manning et al, 2001 ; Manning et al, 2007 ; Coates et al, 2009 ; Fischer Pedersen et al, 2021 ).…”
Section: Prakriti Based Noninvasive Risk Stratification In P...mentioning
confidence: 99%